2010
DOI: 10.1538/expanim.59.47
|View full text |Cite
|
Sign up to set email alerts
|

Indirect ELISA and Indirect Immunofluorescent Antibody Assay for Detecting the Antibody against Murine Norovirus S7 in Mice

Abstract: Abstract:To evaluate murine norovirus (MNV) infection in laboratory mice, we attempted to develop an enzyme-linked immunosorbent assay (ELISA) system and an indirect immunofluorescent antibody (IFA) assay for detecting the anti-MNV-S7 antibody in mice. MNV-S7, which was isolated in Japan, was used in both assays. The antigen for ELISA was prepared by ultracentrifugation of culture supernatants of RAW 264 cells infected with MNV-S7. Positive sera were obtained from 6-week-old, female C57BL/6JJcl mice inoculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 20 publications
0
23
0
3
Order By: Relevance
“…Those constructs produce viral progeny, but the infectivity of the human strains could not be demonstrated because of the lack of a permissive cell system. In contrast, a construct of an MNV-S7 strain, which was initially isolated from mouse stool in Japan (15), produced infectious virions in several cell lines, including RAW264.7 cells and other non-mouse-derived cell lines such as HEK293T cells and COS7 cells. Taken together with the results of Guix et al (10), our results showed that, if the norovirus genome is provided intracellularly, infectious particles can be produced even in cells that are not…”
mentioning
confidence: 99%
“…Those constructs produce viral progeny, but the infectivity of the human strains could not be demonstrated because of the lack of a permissive cell system. In contrast, a construct of an MNV-S7 strain, which was initially isolated from mouse stool in Japan (15), produced infectious virions in several cell lines, including RAW264.7 cells and other non-mouse-derived cell lines such as HEK293T cells and COS7 cells. Taken together with the results of Guix et al (10), our results showed that, if the norovirus genome is provided intracellularly, infectious particles can be produced even in cells that are not…”
mentioning
confidence: 99%
“…As these previous studies indicate that the effects of MNV infection on experiments in mice cannot be generalized, MNV-free mice are recommended for use in biomedical research. Thus, MNV infection in laboratory mouse colonies are monitored periodically by immunological methods such as the enzyme-linked immunosorbent assay [9] and multiplexed fluorescent immunoassay [8], because MNV is believed to comprise a single serogroup [16]. MNV infection in colonies may also be monitored by conventional reverse transcription-polymerase chain reaction (RT-PCR) assays including nested RT-PCR [8], [26]–[30].…”
Section: Introductionmentioning
confidence: 99%
“…This virus is highly prevalent among laboratory mice, and it is symptomless in immunologically normal mice [3,9,10,14,17,18,23]. Karst et al showed that susceptibility to this virus is not substantially increased by deleting the recombination activating gene 1 (Rag1) or Rag2 gene-dependent specific immunity [7].…”
Section: Introductionmentioning
confidence: 99%
“…serological [5,6,9,18] and rT-PCr assays [2,5,6,10,14] have been widely used to detect MnV infections. in particular, the use of rT-PCr has shown that mice experimentally inoculated with an MnV strain (MnV-2, MnV-3, or MnV-4) have detectable viruses in the feces from day 2 to week 8 post infection [5], revealing that mice can become persistently infected and shed virus in the feces for prolonged periods.…”
Section: Introductionmentioning
confidence: 99%